Synthesis and structure activity relationship of 1, 3-benzo-thiazine-2-thiones as selective HDAC8 inhibitors - Wolff, Benjamin; Jänsch, Niklas; Sugiarto, Wisely Oki; Frühschulz, Stefan; Lang, Maraike; Altintas, Rabia; Oehme, Ina; Meyer-Almes, Franz-Josef (European journal of medicinal chemistry, 2019)
Human histone deacetylase 8 (HDAC8) is a highly promising target for neuroblastoma and other types of cancer. Several HDAC inhibitors are approved for the treatment of special cancer subtypes or are evaluated in clinical trials. By far the most drugs or drug candidates contain a hydroxamate group that chelates the catalytic zinc ion within HDACs. Most hydroxamate inhibitors are more or less unselective, although there are considerable exceptions demonstrating the general feasibility to develop at least HDAC isoenzyme selective inhibitors. In addition, hydroxamates have recently come under discussion regarding their potential for mutagenicity. Recently, PD-404,182 was discovered as a selective and potent non-hydroxamate inhibitor of HDAC8. However, this active compound turned out to be decomposed in the presence of glutathion (GSH). Here, we describe the synthesis of significantly improved analogs of PD-404,182 that demonstrate both, great selectivity for HDAC8 and also chemical stability in the presence of GSH. The compounds are characterized with respect to structure-activity relationship, binding mode and target engagement in neuroblastoma cells by combining biochemical and biophysical methods with chemoinformatics.
Gesehen am 20.02.2020